2022
DOI: 10.2174/18749445-v15-e2206130
|View full text |Cite
|
Sign up to set email alerts
|

The Content of Breast Milk and the Challenges Experienced by Breastfeeding Mothers during the COVID-19 pandemic: A Systematic Review

Abstract: Introduction: Every postpartum mother is recommended to breastfeed her baby because breast milk is the main need of newborns. The COVID-19 pandemic has had an impact on life in various aspects, including on the breastfeeding mothers, especially if they suffer from COVID-19 infection. Aim: The study aims to provide comprehensive evidence regarding potential virus transmission and antibody transfer through breastmilk and the experiences of mothers related to breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, we must consider the probability of COVID-19 infection during breastfeeding, especially concerning skin contact with the breast. Potential antibodies against COVID-19 infections in breast milk include IgA and IgG [24].…”
Section: Resultsmentioning
confidence: 99%
“…However, we must consider the probability of COVID-19 infection during breastfeeding, especially concerning skin contact with the breast. Potential antibodies against COVID-19 infections in breast milk include IgA and IgG [24].…”
Section: Resultsmentioning
confidence: 99%
“…The WHO consistently advised breastfeeding support during the COVID-19 pandemic, however many breastfeeding mothers reported that they did not receive enough support [3]. During COVID-19 pandemic, the support from the family is essensial to ensure that mothers breastfeed properly [21]. Mothers that confirmed of COVID-19 need to pay attention to the symptoms that occur during breastfeeding while mothers with severe symptoms of COVID-19 could be advised to get donor milk for the baby.…”
Section: Discussionmentioning
confidence: 99%
“…Any surfaces to be touched must also be routinely cleaned and disinfected. In cases where a mother is severely ill with COVID-19, is suspected of having the virus, or experiences other complications serving as an obstacle to breastfeeding, expressing milk safely is crucial [4]. The use of relactation (restarting breastfeeding after a gap) or donor human milk from certified banks can be used in critical maternal cases.…”
Section: Introductionmentioning
confidence: 99%